NaNbO3/Eumelanin composite: A new photocatalyst under visible light - Fernandes, Daiane; Raubach, Cristiane W.; Ferrer, Mateus M.; Jardim, Pedro L.G.; Graeff, Carlos Frederico de O. [UNESP]; Moreira, Mario L.; Moreira, Eduardo C.; Mastelaro, Valmor R.; da S. Cava, Sergio (Elsevier, 2023)
Sodium niobate (NaNbO3) is a semiconductor with many potential technological applications and, among them, it is considered a promising photocatalyst. However, it only absorbs ultraviolet light, limiting its use in light-dependent processes. Therefore, in this work we synthesized NaNbO3 nanoparticles quickly and used them to prepare a NaNbO3/Eumelanin composite with photocatalytic activity under visible light. Eumelanin was extracted from human hair and is a pigment responsible for the brown-black coloration, abundant in fauna and flora. The results showed that the composite successfully degraded the Rhodamine B dye. Therefore, this study presents a photocatalyst solution with better use of light and serves as inspiration for the development of new photocatalysts.
Keywords: Eumelanin; Photocatalysis; Sodium niobate; Visible light